Drivers of perceived land tenure (in)security: Empirical evidence from Ghana. (July 2017) - Ghebru, Hosaena; Lambrecht, Isabel
Highlights: We identify a knowledge gap on factors associated with perceived tenure security. We analyze factors driving tenure security for rural households in Ghana. Gender, social status, social and economic characteristics are critical. Individually, farmers feel more secure on purchased or inherited land. Collectively, tenure security is lower in communities with more active land markets. Abstract: Tenure security is believed to be critical in spurring agricultural investment and productivity. Yet what improves or impedes tenure security is still poorly understood. Using household- and plot-level data from Ghana, this study analyses the main factors associated with farmers' perceived tenure security. Individually, farmers perceive greater tenure security on plots acquired via inheritance than on land allocated by traditional authorities. Collectively, however, perceived tenure security lessens in communities with more active land markets and economic vibrancy. Plots held by migrant households and women in polygamous households are perceived as less tenure secure, while farmers with political connections are more confident about their tenure security.